In vivo structural imaging in rats reveals neuroanatomical correlates of behavioral sub‐dimensions of cocaine addiction - Cannella, Nazzareno; Spanagel, Rainer (Addiction biology, 2018)
Abstract Cocaine addiction is a multi?dimensional behavioral disorder characterized by a loss of control over cocaine taking despite of detrimental consequences. Structural MRI studies have revealed association between cocaine consumption and gray matter volume (GMV) in cocaine?addicted patients. However, the behavioral correlates of GMV in cocaine addiction are poorly understood. Here, we used a DSM?IV?based rat model of cocaine addiction with high face validity for structural imaging. According to three behavioral sub?dimensions of addiction, rats were separated into two groups showing either addict?like or non?addict?like behavior. These behavioral sub?dimensions were (1) the inability to refrain from drug?seeking and taking, (2) high motivation for the drug, and (3) maintained drug use despite negative consequences. In these rats, we performed structural MRI with voxel?based morphometry and analyzed the interaction of GMV with behavioral sub?dimensions in cocaine?addicted rats. Our major findings are that GMV differentially correlate with the inability to refrain from drug?seeking and taking in addict?like and non?addict?like rats within the somatosensory cortices and the amygdala. High motivation for the drug differentially correlates with GMV in addict?like and non?addict?like rats within the medial prefrontal cortex, and maintained drug use despite negative consequences differentially correlates with GMV in these two groups of rats within the periaqueductal gray. Our results demonstrate that the behavioral differences characterizing addict?like and non?addict?like rats in each behavioral sub?dimension of addiction are reflected by divergent covariance with GMV. We conclude that structural imaging provides specific neuroanatomical correlates of behavioral sub?dimensions of addiction.
First published: 23 February 2017
Gesehen am 13.04.2018